HUBUNGAN GAYA KEPEMIMPINAN SITUASIONAL DAN EFIKASI DIRI DENGAN KINERJA GURU SEKOLAH DASAR KECAMATAN RANCAKALONG KABUPATEN SUMEDANG - Tita Agustini; Yuyun Elizabeth Patras; Tita Rosita (Universitas Pakuan, 2022)
THE RELATIONSHIP OF SITUATIONAL LEADERSHIP STYLE AND SELF EFFICACY TO THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS AT KECAMATAN RANCAKALONG SUMEDANG DISTRICTThis study was intended to formulate efforts that could be implemented in order to improve teacher’s performance by studying its relationship with situational leadership style and self-efficacy. The population of this study were 183 PNS teachers and 126 samples were selected using the Yamane formula with an error tolerance was 5%.. Data were collected using an instrument in the form of questionnairies and analyzed by descriptive and inferential statistical analysis. The results showed that therewere three positive and significant relationships. Firstly, there was a positive and significant relationship between situational leadership style and the performance of PNS teacher, where the correlation coefficient was 0.648. Secondly, there was a positive and significant relationship between self-efficacy and teacher performance, where the correlation coefficient value was 0.585. Thirdly, there was a positive and significant relationship between situational leadership style and self-efficacy altogether with teacher performance, where the correlation coefficient value was 0.719.